2018
DOI: 10.18016/ksudobil.389059
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye'de Bir Deniz Akvaryumunda Humpback Red Snapper (Lutjanus gibbus Foorsskal, 1775) ve Golden Trevally'de (Gnathanodon speciosus Foorsskal, 1775) Vibriozisin Teşhisi

Abstract: This study was carried out to determine the reason of mortalities in humpback red snapper (Lutjanus gibbus) and golden trevally (Gnathanodon speciosus) kept in a marine aquarium in Turkey. Moribund fish showed diffuse haemorrhages on upper and lower jaws, superficial and ulcerative skin lesions, tail rot and pale gills. Internally, clear fluid in peritoneal cavity and pale liver were observed. The isolated bacteria were identified as Vibrio harveyi according to their morphological, physiological, biochemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, a recent review of the literature on these species revealed that most of them have been studied by researchers from countries which compete with Indonesia in international aquaculture markets. For example, all Lutjanus species selected in this study had been studied for their culture potential as far back as 2005, which was 6 years prior the commencement of this study (Wang et al, ; Yardimci, Turgay, & Karatas, ). Two species of Trevally in this study were also researched by other developing countries such as Bangladesh (Abdussamad, Kasim, & Balasubramanian, ) and relatively recently by a research institute in Indonesia (Suprayudi, Ihu, Utomo, & Ekasari, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent review of the literature on these species revealed that most of them have been studied by researchers from countries which compete with Indonesia in international aquaculture markets. For example, all Lutjanus species selected in this study had been studied for their culture potential as far back as 2005, which was 6 years prior the commencement of this study (Wang et al, ; Yardimci, Turgay, & Karatas, ). Two species of Trevally in this study were also researched by other developing countries such as Bangladesh (Abdussamad, Kasim, & Balasubramanian, ) and relatively recently by a research institute in Indonesia (Suprayudi, Ihu, Utomo, & Ekasari, ).…”
Section: Discussionmentioning
confidence: 99%